Non-Hodgkin lymphoma, body mass index and cytokine polymorphisms: a pooled analysis from the InterLymph consortium - Kane, Eleanor (Cancer Epidemiol Biomarkers Prev, 2015)
BACKGROUND: Excess adiposity has been associated with lymphomagenesis, possibly mediated by increased cytokine production causing a chronic inflammatory state. The relationship between obesity, cytokine polymorphisms and selected mature B-cell neoplasms is reported. METHOD: Data on 4979 cases and 4752 controls from nine American/European studies from the InterLymph consortium (1988–2008) were pooled. For diffuse large B-cell lymphoma (DLBCL), follicular lymphoma (FL) and chronic lymphocytic leukaemia/small lymphocytic lymphoma (CLL/SLL), joint associations of body mass index (from self-reported height and weight) and 12 polymorphisms in cytokines IL1A (rs1800587), IL1B (rs16944, rs1143627), IL1RN (rs454078), IL2 (rs2069762), IL6 (rs1800795, rs1800797), IL10 (rs1800890, rs1800896), TNF (rs1800629), LTA (rs909253), and CARD15 (rs2066847) were investigated using unconditional logistic regression. BMI-polymorphism interaction effects were estimated using the relative excess risk due to interaction (RERI). RESULTS: Obesity (BMI≥30kg m(−2)) was associated with DLBCL risk (OR=1.33, 95%CI 1.02–1.73), as was TNF-308GA+AA (OR=1.24, 95%CI 1.07–1.44). Together, being obese and TNF-308GA+AA increased DLBCL risk almost two-fold relative to those of normal weight and TNF-308GG (OR=1.93 95%CI 1.27–2.94), with a RERI of 0.41 (95%CI −0.05,0.84, P(interaction)=0.13). For FL and CLL/SLL, no associations with obesity or TNF-308GA+AA, either singly or jointly, were observed. No evidence of interactions between obesity and the other polymorphisms were detected. CONCLUSIONS: Our results suggest that cytokine polymorphisms do not generally interact with BMI to increase lymphoma risk but obesity and TNF-308GA+AA may interact to increase DLBCL risk. IMPACT: Studies using better measures of adiposity are needed to further investigate the interactions between obesity and TNF-308G>A in the pathogenesis of lymphoma.